EFFECTS OF SEASONAL AIR TEMPERATURES AND LIGHT ON LEAF TRAITS AT ATLANTIC MONTANE FOREST, BRAZILIAN SOUTHEAST - Marchiori, Nidia Mara; Silva, Janaina Gomes da; Santos, Fernanda Cassemiro dos; Domingues, Leonardo Moreno; Freitas, Helber Custodio de [UNESP]; Rocha, Humberto Ribeiro da; Camargo, Plinio Barbosa de; Marinho Aidar, Marcos Pereira (Univ Federal Lavras-ufla, 2019)
Seasonal variation of temperature could place physiological constraints on the distribution and performance of tropical forest plants, associated with light and water availability. A simple way to assess the relationship between temperature and plant physiology is through the characterization of leaf traits. The main aim of this study was to evaluate, through foliar parameters, the responses of plants to inherent seasonality. A 0.09 ha plot was installed near the flux tower and albedo sensors at Montane Ombrophilous Dense Forest (MODF) - Santa Virginia Nucleus. At the peak of the dry and wet seasons, the electron transport rate (ETR) and photosynthetic pigments were measured. The results indicated that in MODF, cold and light availability are the main factors that could be influencing the physiology of species, demonstrated by high ETR in the wet season (197.4 mu mol e-m(-2)s(-1)) compared to the dry season (87.4 mu mol e-m(-2)s(-1)). Photosynthetic pigments varied between seasons, we observed higher chlorophyll b content (p<0.05), and lower content of carotenoids and xanthophylls (p<0.01) and Chl a/b (p<0.01) in the dry season. The low temperatures and irradiance influenced metabolic activity.
Keywords: Albedo; Chlorophyll; Carotenoids; Xantophylls